Enhanced Singlet Oxygen Generation in Oxidized Graphitic Carbon Nitride for Organic Synthesis. Issue 32 (6th June 2016) - Wang, Hui; Jiang, Shenlong; Chen, Shichuan; Li, Dandan; Zhang, Xiaodong; Shao, Wei; Sun, Xianshun; Xie, Junfeng; Zhao, Zhi; Zhang, Qun; Tian, Yupeng; Xie, Yi
Abstract : Experimental data reveal that the incorporation of carbonyl groups into polymer matrix can significantly enhance singlet oxygen ( 1 O2 ) generation and suppress production of other reactive oxygen species. Excitonic processes investigated by phosphorescence spectroscopy reveal enhanced triplet‐exciton generation in the modified g‐C3 N4, which facilitate 1 O2 generation through an energy transfer process. Benefiting from this, the modified g‐C3 N4 shows excellent conversion and selectivity in organic synthesis.